A systematic scoping review of irrigation development and agricultural water management in South Africa - Mabhaudhi, T.; Dirwai, Tinashe Lindel; Taguta, C.; Kanda, E. K.; Nhamo, L.; Cofie, Olufunke O. (Springer, 2025)
An estimated 80% of Africa’s population depends on agriculture; hence, efficient agricultural water management (AWM) is crucial for enhancing agricultural and water productivity and building climate resilience across different farming scales to ensure food security. Approximately 90% of sub-Saharan Africa’s agriculture is rain-fed, and the bulk of the farmers are classified as smallholder farmers, constituting 70% of the continent’s population. Climate change (CC) and climate variability (CV) have increasingly imposed yield penalties on Africa’s irrigated and non-irrigated farming sectors. This has put significant pressure on the African farmer to produce more on less water. As such, the African Union (AU), through the AU-Irrigation Development and Agricultural Water Management (AU-IDAWM) framework, proposed four IDAWM pathways as potential countermeasures to yield penalties. Despite inroads made to equip the African farmer with extension services, a dearth of information related to performance challenges faced in the continent’s irrigation fraternity exists. This information is vital as a feedback loop to identify opportunities, challenges, and potential investment gaps to boost irrigation development in the continent. Therefore, using a South African case study, this research sought to assess the existing knowledge, gaps, challenges, and opportunities related to irrigation development and agricultural water management. PRISMA-P protocols guided the study. The SPIDER (Sample, Phenomenon of Interest, Design, Evaluation, and Research type) framework informed the eligibility criteria, which we used to formulate the inclusion–exclusion criteria. The different AU-IDAWM exhibited varied developments in infrastructural and governance structures. The AWM practices exhibited overlaps than variances under the rain-fed, FLID, and modernisation pathways.